Pengaruh Model Pembelajaran ALC Berbantuan Media Quizizz Untuk Meningkatkan Literasi Numerasi Matematika Siswa Sekolah Dasar - I Putu Suardipa; Ni Nyoman Lisna Handayani; Ni Luh Dewi Budayani (STAHN Mpu Kuturan Singaraja, 2023)
The research aims to find out the significant effect of the ALC Model Assisted by Quizizz Media with Conventional Learning Models to Improve Mathematical Numeracy Literacy for IV elementary School Students. This research has quasi-experimental. The total population in this study was 161 students and research sample is 60 students with 30 experimental class students and 30 control class students. Based on the hypothesis that has been tested that, data analysis using independent t-test for N-Gain Score shows that df 30 + 30 - 2 = 58 with the value of tcount = 3,341 at a significant of 5%, the ttable value is obtained, namely 2,002. From the calculations results is known that tcount > ttable is 3,341 > 2,002 and Sig. (2-tailed) < 0.05 (0.001 < 0.05). This shows there is a significant difference in the effect of mathematical numeracy literacy between students who study with the ALC Model assisted by Quizizz media with the Conventional Model to improve mathematical numeracy literacy for 4 grade students of SD Cluster 3 Tejakula Village in the 2021/2022 academic year.